Patient and Societal Value Functions for the Testing Morbidities Index. (August 2013) - Swan, J. Shannon; Kong, Chung Yin; Lee, Janie M.; Itauma, Omosalewa; Halpern, Elkan F.; Lee, Pablo A.; Vavinskiy, Sergey; Williams, Olubunmi; Zoltick, Emilie S.; Donelan, Karen
Background: We developed preference-based and summated scale scoring for the Testing Morbidities Index (TMI) classification, which addresses short-term effects on quality of life from diagnostic testing before, during, and after testing procedures.Methods: The two TMI preference functions use multiattribute value techniques; one is patient-based and the other has a societal perspective, informed by 206 breast biopsy patients and 466 (societal) subjects. Because of a lack of standard short-term methods for this application, we used the visual analog scale (VAS). Waiting tradeoff (WTO) tolls provided an additional option for linear transformation of the TMI. We randomized participants to 1 of 3 surveys: The first derived weights for generic testing morbidity attributes and levels of severity with the VAS; a second developed VAS values and WTO tolls for linear transformation of the TMI to a "dead-healthy" scale; the third addressed initial validation in a specific test (breast biopsy). The initial validation included 188 patients and 425 community subjects. Direct VAS and WTO values were compared with the TMI. Alternative TMI scoring as a nonpreference summated scale was included, given evidence of construct and content validity.Results: The patient model can use an additive function, whereas the societal model is multiplicative. Direct VAS and the VAS-scaled TMI were correlated across modeling groups (r = 0.45–0.62). Agreement was comparable to the value function validation of the Health Utilities Index 2. Mean absolute difference (MAD) calculations showed a range of 0.07–0.10 in patients and 0.11–0.17 in subjects. MAD for direct WTO tolls compared with the WTO-scaled TMI varied closely around 1 quality-adjusted life day.Conclusions: The TMI shows initial promise in measuring short-term testing-related health states.